Вплив кріоконсервованих експлантів плаценти на перебіг експериментального синдрому полікістозних яєчників - Прокопюк, В. Ю.; Гольцев, А. М.; Прокопюк, О. C.; Сомова, К. В.; Логінова, О. О. (Вісник проблем біології і медицини. – 2018. – Вип. 1, т. 1 (142). – С. 167–171., 2018)
Синдром полікістозних яєчників діагностується у 5-15% жінок репродуктивного віку. Він проявляється в ановуляції, гіперандрогенії, безплідді, порушенні обміну вуглеводів. Ці процеси коригуються при вагітності, терапії стовбуровими клітинами, препаратами плаценти. Метою роботи було визначення впливу кріоконсервованих експлантів плаценти на перебіг синдрому полікістозних яєчників. Патологію моделювали на щурах лінії Wistar введенням мефіпрістону. Показано, що використання кріоконсервованих експлантів плаценти призводить до нормалізації естрального циклу, збільшення кількості зростаючих фолікулів, зменшення кількості кіст, гіперплазії ендометрію, поліпшенню репродуктивних показників. / / / / / / / / / / Polycystic ovary syndrome (POS) is diagnosed in 5-15% of women in reproductive age. It manifests in anovulation, hyperandrogenism, infertility and carbohydrate metabolism failure. These processes changing during pregnancy, stem cell therapy. It can be supposed, that placental derivatives may be used for POS treatment. The aim of the work was to study the effect of cryopreserved placental explants (CPE) on the progression of experimental POS. Methods. POS was modeled on Wistar rats by the mefipristone injection. Animals were divided into three groups: 1 – animal with the model of POS without treatment, 2 – animal with POS, treated by 70 mg of CPE, 3 – intact animals. Morphological changes in ovaries, uterus, reproductive indices was studied. Results. A month after POS modeling, all experimental animal had an estrogenic type of vaginal cytology with superficial epithelial cells. Animal without treatment had cystic changes in the ovaries. In some cases, large cysts – up to 5 mm, sometimes the cysts reached 2-3 mm, with a hemorrhages in the cavity. Also were noticed the reducing number of secondary follicles (in the growth stage) and yellow bodies. The number of primordial and primary follicles did not change. The hyperplasia of endometrium was noticed in the uterus. None of animals became pregnant. The presence of a small number of yellow bodies in the ovaries could be explained by luteinisation without ovulation or unavailability of endometrium to implantation. When study the group with POS, treated by CPE, the number of ovarian cysts was significantly lower, the number of yellow bodies and secondary follicles were increased, that indicate some normalization of folliculogenesis. The hyperplasia of endometrium were decreased. Animals with POS, treated by CPE were pregnant in half of the cases. In pregnant animals, the number of yellow bodies, implantation sites, and the number of live fetuses were reduced in comparison with intact animals. However, the greatest difference was in the number of yellow bodies and implantation sites indicates reproductive loss at the implantation stage due to the lack of endometrium preimplantation preparedness. Conclusions. The study suggests that the use of cryopreserved placental explants in the anti-progestin model of POS allows restore of folliculogenesis, endometrium structure and fertility. / / / / / / / / / / Синдром поликистозных яичников диагностируется у 5-15% женщин репродуктивного возраста. Он проявляется в ановуляции, гиперандрогении, бесплодии, нарушении обмена углеводов. Эти процессы корригируются при беременности, терапии стволовыми клетками, препаратами плаценты. Целью работы было определение влияния криоконсервированных эксплантов плаценты на течение синдрома поликистозных яичников. Патологию моделировали на крысах линии Wistar введением мефипристона. Показано, что использование криоконсервированных эксплантов плаценты приводит к нормализации эстрального цикла, увеличению количества растущих фолликулов, уменьшению количества кист, гиперплазии эндометрия, улучшению репродуктивных показателей
Effect of cryopreserved placental explants on the course of experimental polycystic ovary syndrome
Влияние криоконсервированных эксплантов плаценты на течение экспериментального синдрома поликистозных яичников
Вплив кріоконсервованих експлантів плаценти на перебіг експериментального синдрому полікістозних яєчників / В. Ю. Прокопюк, А. М. Гольцев, О. C. Прокопюк [та ін.] // Вісник проблем біології і медицини. – 2018. – Вип. 1, т. 1 (142). – С. 167–171. doi.org/10.29254/2077-4214-2018-1-1-142-167-171
Keywords: синдром полікістозних яєчників; плацента; кріоконсервування; щури; непліддя; __________________________________________________________________________; polycystic ovary syndrome; placenta; cryopreservation; rats; infertility; __________________________________________________________________________; синдром поликистозных яичников; плацента; криоконсервирование; крысы; бесплодие